2020
DOI: 10.1186/s12984-020-00780-5
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and non-invasive brain stimulation for rehabilitation applications: a systematic review

Abstract: The present article reports the results of a systematic review on the potential benefits of the combined use of virtual reality (VR) and non-invasive brain stimulation (NIBS) as a novel approach for rehabilitation. VR and NIBS are two rehabilitation techniques that have been consistently explored by health professionals, and in recent years there is strong evidence of the therapeutic benefits of their combined use. In this work, we reviewed research articles that report the combined use of VR and two common NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…3 Growing evidence has revealed that VR has the potential to generate effective rehabilitation environments, which are possibly individualized, safe, and multimodal simulations. 2,[4][5][6][7][8] Moreover, VR has the potential to provide the key elements of neuroplasticity (i.e., feedback, repetition, intensity, and taskspecific training), which are not usually possible in conventional physical therapies 9 but are helpful to speed up the recovery of UEs poststroke. [10][11][12] Basic neuroscience behind VR-based treatment Besides providing external stimulation, VR has additional potential to stimulate the internal sensorimotor system, possibly linked with better functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Growing evidence has revealed that VR has the potential to generate effective rehabilitation environments, which are possibly individualized, safe, and multimodal simulations. 2,[4][5][6][7][8] Moreover, VR has the potential to provide the key elements of neuroplasticity (i.e., feedback, repetition, intensity, and taskspecific training), which are not usually possible in conventional physical therapies 9 but are helpful to speed up the recovery of UEs poststroke. [10][11][12] Basic neuroscience behind VR-based treatment Besides providing external stimulation, VR has additional potential to stimulate the internal sensorimotor system, possibly linked with better functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…VR is an advanced form of a computer‐simulated environment that allows users to “interact” with the virtual objects and the environment within a rendered scenario 3 . Growing evidence has revealed that VR has the potential to generate effective rehabilitation environments, which are possibly individualized, safe, and multimodal simulations 2,4–8 . Moreover, VR has the potential to provide the key elements of neuroplasticity (i.e., feedback, repetition, intensity, and task‐specific training), which are not usually possible in conventional physical therapies 9 but are helpful to speed up the recovery of UEs poststroke 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…For future research, an interesting possibility could be to adopt a mixed approach. Indeed, for motor recovery, different studies have already reported positive effects on the combined use of VR and tDCS [ 173 , 174 , 175 , 176 ] and VR with tele-practice [ 177 ]. In addition, as previously described ( Section 2.2 ), since the combined effect of d-amphetamine with tDCS and language therapy was already successfully investigated in post-stroke aphasia, it would also be interesting to further explore this new approach [ 61 ].…”
Section: General Conclusionmentioning
confidence: 99%
“…Furthermore, some studies have combined virtual walking with transcranial direct current stimulation (tDCS), indicating the combination of these two tools to strongly reduce NP suggesting a synergistic effect [ 44 , 54 , 55 ]. Findings indicate that VR is an effective analgesic intervention for the treatment of NP in people with SCIs, with some studies identifying its short, medium, and long-term effects, especially when it is used in combination with tDCS.…”
Section: Real Sci In a Virtual Worldmentioning
confidence: 99%